The role of glycoprotein Ibalpha and von Willebrand factor interaction in stroke development - Stoll, G.; Kleinschnitz, C.; Nieswandt, B. (Hämostaseologie, 2010)
Ischaemic stroke is a devastating disease with limited treatment options due to numerous uncertainties regarding the underlying pathophysiology. The contribution of glycoprotein (GP)Ibα and von Willebrand factor (VWF) in stroke development has only recently been established in mice. Complete blockade of GPIbα led to a significant reduction of infarct volumes in mice undergoing one hour of transient middle cerebral artery occlusion (tMCAO). High shear-induced changes in VWF confirmation are a prerequisite for VWF binding to collagen and GPIbα expressed on platelets. Importantly, transgenic VWF−/−mice were similarly protected against ischemic stroke after tMCAO, and hydrodynamic injection of a VWF-encoding plasmid restored VWF serum levels and the susceptibility towards stroke. Secreted VWF is rapidly cleaved by ADAMTS13. Accordingly, ADAMTS13 deficient mice developed larger infarction after tMCAO, while infusion of recombinant ADAMTS13 into wild-type mice was strokeprotective. In conclusion, there is compelling evidence that GPIbα/VWF interactions and downstream signaling via phospholipase D1 (PLD1) provide new therapeutic targets in ischemic stroke.
Keywords: Von Willebrand factor; thrombus formation; cerebral ischaemia